Cybernetics, warfare and discourse : the cybernetisation of warfare in Britain - Tsirigotis, Anthimos Alexandros (Palgrave MacMillan, 2020)
Contents: Chapter 1:Introduction -- Chapter 2: War and Military Power in the Information Age -- Chapter 3: Cybernetics, War and Power -- Chapter 4: British Defence and Security Policy-Making Practice -- Chapter 5: The Cybernetisation of the British Discourse on War -- Chapter 6: The Cybernetisation of the British Defence and Security Policy-Making Genre -- Chapter 7: Strategic Priorities for Britain After 1957 and New Perceptions of Military Power -- Chapter 8: Cybernetisation as a Tool of Analysis.